Genetic polymorphism of haemostatic system in patients with venous disfunction at mesenchimal dysplasia - Ye. F. Kotovschikova; Ye. I. Buyevich; V. P. Kulikov; V. F. Chudimov; Ye. Pen’kova (Бюллетень сибирской медицины)
.